Is Second-hand Shopping a Solution to the Circular Economy of Clothes? - Lahtinen, Emmi (2025)
The fashion industry today is overproducing clothing and textiles, and the rapidly increasing textile waste is a burden to our environment. To fix this, second-hand fashion has been suggested as a solution to solve the problem of excessive textile waste and make fashion consumption more sustainable. However, there is a possibility that second-hand might lead to more, not less, consumption of clothing. Therefore, the purpose of this thesis is to find out how the increasing prominence of second-hand culture has affected consumers’ consumption habits of clothing. There are two concepts that are relevant for this topic: rebound effect and moral self-licensing. To examine the phenomenon, a qualitative study was conducted to find out how second-hand has affected the consumption habits of female consumers in between ages 20-35 who live in the Helsinki metropolitan area. As a result of 12 semi-structured interviews, it can be concluded that rebound effect is real and second-hand fashion indeed seems to cause more consumption of clothes. However, the respondents do not identify it. The results show that respondents buy second-hand garments spontaneously without a specific need, and once their closet is too full, they sell unnecessary garments in second-hand channels, therefore keeping second-hand markets alive. In addition, respondents feel that selling and buying second-hand is an ecological act and makes them feel good, which indicates that moral self-licensing occurs in the interviewees’ consumption behaviour. My findings suggest that second-hand has impacted the consumption habits of clothing by giving an additional way to consume fashion. According to this study, second-hand does not replace buying new. However, more research should be conducted about the impacts of the rebound effect in order to discover better solutions to the unsustainable clothing consumption.